Media społecznościowe w rękach młodych ludzi - Konieczna, Ewelina (Studia Edukacyjne, 2020)
Popular media culture has been a vital resource through which youth generations have defined themselves, their desires, and their hopes and dreams. This continues to be reflected in the dynamic ways that the youth are using digital media to shape their everyday lives. As a result, young people are constantly creative; they acquire new skills and make up groups and communities in the media culture. The purpose of the reflections in the article is a look at the media practices of young people and an attempt to find an answer to the question how the young generation uses social media for communication and participation in culture and how social media change media culture.